Diagnostic criteria for computer-aided electrocardiographic 15-lead system. Evaluation using 12 leads and Frank orthogonal leads with vector display. Issue 12 (December 1976) - Talbot, S; Dreifus, L S; Watanabe, Y; Chiang, R; Morris, K; Reich, M
Abstract : The criteria for the diagnosis of myocardial infarction and ischaemic heart disease by an automated 15-lead computer-aided electrocardiographic system were examined using electrocardiograms of 543 patients. Errors in the electrocardiographic diagnosis were evaluated for each lead system (Frank orthogonal 3-lead, 12-lead, and hybrid 15-lead) using clinical and catheterization data for definitive diagnosis before review of the electrocardiograms and their reports. The effects of combinations of these diagnoses and additional ventricular conduction defects were also studied. Myocardial infarction and left ventricular hypertrophy were more reliably diagnosed using 3-lead and 12-lead systems together than with either system alone. The most sensitive criteria for anterior infarction were a Q/R ratio in Z less than 0-1 and loss of the first 20 ms of anterior forces in the horizontal and sagittal planes of the vectorcardiogram. However, false positive results were frequent, particularly in association with left ventricular hypertrophy, non-specific intraventricular conduction defects, and left bundle branch system block. Our V lead criteria were more specific whether or not these associated conditions were present. No single criterion with an acceptable false positive rate could be found to be sensitive for inferior infarction in all situations. Our most sensitive criteria were those based on the limb leads, and the presence of superior forces for the first 30 ms in the frontal plane of the vectorcardiogram, but these were better in combination. Limb lead criteria were the most specific. False positive results for inferior infarction were more frequent in the presence of left ventricular hypertrophy or ventricular conduction defects other than left anterior hemiblock. ST and T wave abnormalities were more apparent in the 12 leads than in the orthogonal leads. Specificity and sensitivity of criteria were poor, and specificity was decreased and sensitivity was not significantly improved by combining 3-lead with 12-lead criteria. Because of frequent measurement errors of ST, T, and also Q waves by the computer programme, in practice we have achieved increased sensitivity in the diagnosis of ischaemia and infarction with the combination of 3-lead and 12-lead systems. It is concluded that errors of diagnosis by a computer-aided system can be reduced by using multiple leads and that both 12-lead and orthogonal 3-lead systems are necessary for optimal computer diagnosis of left ventricular hypertrophy, myocardial infarction, and ischaemia.